Anti-CXCR4 Antibody Combined With Activated and Expanded Natural Killer Cells for Sarcoma Immunotherapy - Vela, Maria; Bueno, David; González-Navarro, Pablo; Brito, Ariadna; Fernández, Lucía; Escudero, Adela; Valentín, Jaime; Mestre-Durán, Carmen; Arranz-Álvarez, Marina; Pérez de Diego, Rebeca; Mendiola, Marta; Pozo-Kreilinger, José Juan; et al. (Frontiers in Immunology, 2019)
Sarcoma is one of the most severe forms of pediatric cancer and current therapies -chemotherapy and surgery- fail to eradicate the disease in half of patients. Preclinical studies combining new therapeutic approaches can be useful to design better therapies. On one hand, it is known that CXCR4 expression is implicated in rhabdomyosarcoma progression, so we analyzed relapses and chemotherapy-resistant rhabdomyosarcoma tumors from pediatric patients and found that they had particularly high levels of CXCR4 expression. Moreover, in assays in vitro, anti-CXCR4 blocking antibody (MDX1338) efficiently reduced migration and invasion of alveolar rhabdomyosarcoma RH30 cells. On the other hand, activated and expanded natural killer (NKAE) cell therapy showed high cytotoxicity against sarcoma cells in vitro and completely inhibited RH30 tumor implantation in vivo. Only the combination of MDX1338 and NKAE treatments completely suppressed metastasis in mice. In this study, we propose a novel therapeutic approach based on anti-CXCR4 blocking antibody in combination with NKAE cell therapy to prevent rhabdomyosarcoma tumor implantation and lung metastasis. These results provide the first evidence for the efficacy of this combined immunotherapy for preventing sarcoma disease dissemination.